2019 14th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2019
DOI: 10.1109/hri.2019.8673077
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Tutoring Using Social Robots: A Large-Scale Study

Abstract: We present a large-scale study of a series of seven lessons designed to help young children learn English vocabulary as a foreign language using a social robot. The experiment was designed to investigate 1) the effectiveness of a social robot teaching children new words over the course of multiple interactions (supported by a tablet), 2) the added benefit of a robot's iconic gestures on word learning and retention, and 3) the effect of learning from a robot tutor accompanied by a tablet versus learning from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 35 publications
8
94
1
Order By: Relevance
“…Conversational systems lack understanding of meaning and context and typically act on scripts in a pre-designed type of conversation (Serholt, 2018). Although there are noteworthy examples of somewhat long-term studies of autonomous social robots being conducted in classrooms (Serholt and Barendregt, 2016;Alves-Oliveira et al, 2019;Davison et al, 2020), many studies still require some degree of teleoperation for the interaction to work smoothly, particularly when it comes to verbal communication (Kory-Westlund and Breazeal, 2019;Vogt et al, 2019). This suggests that interaction trouble will likely continue to be a prominent feature of conversational interactions with autonomous social robots.…”
Section: Discussionmentioning
confidence: 99%
“…Conversational systems lack understanding of meaning and context and typically act on scripts in a pre-designed type of conversation (Serholt, 2018). Although there are noteworthy examples of somewhat long-term studies of autonomous social robots being conducted in classrooms (Serholt and Barendregt, 2016;Alves-Oliveira et al, 2019;Davison et al, 2020), many studies still require some degree of teleoperation for the interaction to work smoothly, particularly when it comes to verbal communication (Kory-Westlund and Breazeal, 2019;Vogt et al, 2019). This suggests that interaction trouble will likely continue to be a prominent feature of conversational interactions with autonomous social robots.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, we recommend preregistering the hypotheses and analysis plans before conducting the actual evaluation. 3 Preregistration is still uncommon in NLG and other fields of AI (with a few notable exceptions, like for instance Vogt et al, 2019), but it addresses an important issue with human evaluations. Conducting and analysing a human experiment is like entering a garden of forking paths (Gelman and Loken, 2013): along the way researchers have many choices to make, and even though each choice may be small and seemingly innocuous, collectively they can have a substantial effect on the outcome of the statistical analyses, to the extent that it becomes possible to present virtually every finding as statistically significant (Simmons et al, 2011;Wicherts et al, 2016).…”
Section: Statisticsmentioning
confidence: 99%
“…As a note, there are other studies where the mode of presentation did not have the expected impact. For instance, Vogt et al [51] reported from a study where social robots were used to tutor children in second language learning. They could not find the expected differences in the learning effect between modes that were different in their implementation (tablet only vs. use of a social robot, the latter with and without the use of gestures), although they performed a large-scale study.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%